KCNQ1 Variants Associate with Type 2 Diabetes in Malaysian Malay Subjects - Saif-Ali, Riyadh; Muniandy, Sekaran; Al-Hamodi, Zaid; Lee, Cheng Siang; Ahmed, Khaled A; Al-Mekhlafi, Abdulsalam M; Ismail, Ikram Shah (Annals of the Academy of Medicine, Singapore, 2011)
Introduction: Type 2 diabetes (T2D) candidate gene: potassium voltage-gated channel, KQT-like subfamily, member 1 (KCNQ1) was suggested by conducting a genome wide association study (GWAS) in Japanese population. Association studies have been replicated among East Asian populations; however, the association between this gene and T2D in Southeast Asian populations still needs to be studied. This study aimed to investigate the association of KCNQ1 common variants with type 2 diabetes in Malaysian Malay subjects. Materials and Methods: The KCNQ1 single nucleotide polymorphisms (SNPs): rs2237892, rs2283228, and rs2237895 were genotyped in 234 T2D and 177 normal Malay subjects. Results: The risk allele of the rs2283228 (A) was strongly associated with T2D (OR = 1.7, P = 0.0006) while the rs2237892 (C) was moderately associated with T2D (OR = 1.45, P = 0.017). The recessive genetic models showed that rs2283228 was strongly associated with T2D (OR = 2.35, P = 0.00005) whereas rs2237892 showed a moderate association with T2D (OR = 1.69, P = 0.01). The haplotype block (TCA), which contained the protective allele, correlated with a protection from T2D (OR = 0.5, P = 0.003). Furthermore, the diplotype (CAA-TCA) that contained the protective haplotype was protected against T2D (OR = 0.46, P = 0.006). Conclusion: The KCNQ1 SNPs, haplotypes and diplotypes are associated with T2D in the Malaysian Malay subjects. Key words: Diplotypes, Haplotypes, KCNQ1, SNPs, Type 2 diabetes